Kegiatan Pengabdian kepada Masyarakat Peningkatan Kesadaran Siswa Terhadap perlunya Asupan Gizi Sehat dan Seimbang guna Menunjang Proses Belajar - Alexander Halim Santoso; Fidelia Alvianto; Valentino Gilbert Lumintang (PPNI UNIMMAN, 2025)
Healthy and balanced nutrition plays an important role in supporting students' physical, mental, and academic health, especially during growth. This community service activity aims to increase students' awareness of the importance of a healthy and balanced diet to support the learning process. This activity is carried out by involving nutrition education and nutritional status checks, such as body mass index (BMI), through a school-based approach at SMA St. Yoseph, East Jakarta. Students who have a healthy and balanced nutritional intake tend to have higher learning performance and concentration. Conversely, students with poor nutritional intake are more susceptible to infectious diseases and have lower attendance rates at school. Education provided interactively can increase students' awareness and understanding of the importance of a healthy and balanced nutritional intake. This is expected to be the first step to prevent nutritional disorders and improve the quality of students' health and academics in the future.